Inequalities in reported use of cervical screening in Estonia: results from cross-sectional studies in 2004-2020 - Maria Suurna; Madleen Orumaa; Inge Ringmets; Kersti Pärna (BMC, 2022)
Abstract Background Despite the national cervical cancer (CC) screening program established in 2006, the CC incidence in Estonia in 2020 was still one of the highest in Europe. To better understand the possible barriers among women, the aim of this study was to describe the inequalities in the Pap smear uptake trend in 2004-2020 and to analyse the associations between different factors in Estonia. Methods Weighted data of 25-64-year-old women (N = 6685) from population-based cross-sectional studies of Health Behaviour among Estonian Adult Population in 2004-2020 was used. Linear trends in uptake of Pap smear over time were tested using the Cochrane-Armitage test. Binary logistic regression with interactions was performed to analyse associations between the uptake of Pap smear and sociodemographic, socioeconomic, health-related and lifestyle factors. Crude and adjusted odds ratios with 95% confidence intervals were calculated. Results Prevalence of lifetime uptake of Pap smear increased in 2004-2020 from 50.6 to 86.7% (P < 0.001). From 2004 to 2020, uptake of Pap smear increased significantly among women aged 25-34, 35-44, 45-54 and 55-64, in both ethnicity groups and among women with basic, secondary and higher education (P < 0.001). The gap in Pap smear uptake increased between Estonians and non-Estonians but decreased between education levels over time. Lower lifetime uptake of Pap smear was associated from sociodemographic factors with younger age, being non-Estonian and single, from socioeconomic factors with lower educational level and unemployment, from health indicators with higher body mass index indicating overweight and obesity, presence of chronic disease and depressiveness, and from lifestyle factors with non-smoking. Conclusions Although Pap smear uptake among 25-64 year old women increased significantly in Estonia in 2004-2020, inequalities were found indicating an opportunity for development of targeted CC prevention strategies.